Exploring protective factors through positive psychology and salutogenesis in Danish families with type 2 diabetes. (30th September 2021) - Meldgaard, Julie; Jespersen, Louise Norman; Andersen, Tue Helms; Grabowski, Dan
Summary: People with type 2 diabetes (T2D) live with several challenges, which may enhance the risk of poor mental and physical health. However, despite living with a chronic illness, some individuals manage to achieve a life with positivity and well-being. The objective of this study is to explore the potential of Positive Psychology and Salutogenesis when analyzing how families with one or more members with T2D experience having resources leading to thriving. Data consist of 18 semi-structured family interviews with 38 participants. Data were analyzed using systematic text condensation with the concepts of sense of coherence and upward/downward spirals as the analytical framework. The analysis revealed three overall findings: (i) T2D is perceived as manageable due to general optimism despite living with a chronic illness; (ii) establishing supportive social relations means having the opportunity to share the burden of diabetes; and (iii) achieving an open dialogue and communicating the difficulties of diabetes without straining surroundings with negative illness communication. The three overall findings may reinforce each other in an upward spiral and enhance the sense of coherence. These findings have implications for diabetes management research and our understanding of psychological health in chronic illness. The overall goal is to help people with diabetes create meaning with their illness and make use of their social environment through dialogue and communication in order to increase positivity, optimism and mental health. Lay Summary: Type 2 diabetes is a chronic disease that involves ongoing disease self-management and several challenges, which may cause stress and negatively impact the quality of life. It can be difficult for people with diabetes and their relatives to manage the demanding illness and integrate it into daily life. However, despite living with diabetes, some individuals live a life with good mental health, positivity and well-being. This article uses the analysis of 18 interviews with 38 participants to describe factors influencing mental health in families with one or more members with type 2 diabetes. Factors such as optimism, supportive social relations and open communication all contributed to the family's positivity and mental health. When the families were optimistic about life with diabetes, when they were having and using supportive social relations and when they achieved a dialogue and communicated the difficulties of diabetes, diabetes seemed easier to manage and the burden of the illness where reduced. Optimism, supportive social relations and open illness communication appear connected and enhance one another. The goal is to help people with diabetes create meaning with their illness and make use of their social environment through dialogue in order to increase positivity, optimism and mental health.